HUBUNGAN IKLAN DAN CITRA MEREK DENGAN KEPUTUSAN PEMBELIAN SHAMPO CLEAR PADA SWALAYAN FADILLAH KOTA BENGKULU - Tito Irwanto; Wahyu Hariyadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This study aims to determine the relationship of advertising and brand image with purchase decision of shampo clear on Swalayan Fadillah of Bengkulu City. The sample in this study as many as 50 customers who purchase shampoo clear. The data collection method was used questionaire. The analysis method was used spearman rank correlation and hypothesis test with t test. Advertisement has a strong correlation with purchase decision of shampoo clear on Swalayan Fadillah of Bengkulu City with correlation value of 0.757, means that the better the advertisement made by the company of shampoo clear then the higher of purchase decision of shampoo clear at Swadayan Fadillah Bengkulu City. This result is reinforced by the hypothesis test result that t count is bigger than t table (8,025> 1,677). Thus the result of the hypothesis is H 01 rejected and H a1 accepted. This means that the advertisement has a significant correlation with purchase decision of shampoo clear on Swadayan Fadillah Bengkulu City. Brand image with the decision to purchase decision of shampoo clear on Swadayan Fadillah Bengkulu City has a very strong correlation with a correlation value of 0.831, this means that the better brand image Clear Shampoo then the higher of purchase decision of shampoo clear on Swadayan Fadillah Bengkulu City. This is reinforced by the result of hypothesis test that t count is bigger than t table (10,358> 1,677). Thus the result of the hypothesis is H 02 rejected and H a2 accepted. This means that the brand image has a significant relationship with purchase decision of shampoo clear on Swadayan Fadillah Bengkulu City.